Pemberitaan Berdirinya Khilafah: Analisis Wacana Kritis Pada Tabloid Media Umat - Laode Samsul (DIALEKTIKA: Jurnal Ilmiah Pendidikan Bahasa, Sastra, dan Matematika, 2015)
This research aimed at analyzing the reporting representation of the caliphate establishment formed in Media Ummah Tabloid, the meaning of message, and values of Jurnalist/Media Ideology in representing his news. This research applied qualitative method by critical discourse analysis design of Norman Fairclough.The result of the research was found that: One, representation of the reporting on the establishment of Caliphate was represented superordinately in the rubric of Media Utama with ideological and political oriented. Two, in analysis of micro level or analysis of text, namely combination of inter-word or sentence and coherence and cohesiveness, formed the meaning on the indications of the establishment of Caliphate in 2013. Three, Analysis of Discourse Practice, namely dimension of event of communications related to production process and text consumption shown that the reporter of Media Ummah had Islamic values and ideology.